If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9x+5=5(x-7)
We move all terms to the left:
9x+5-(5(x-7))=0
We calculate terms in parentheses: -(5(x-7)), so:We get rid of parentheses
5(x-7)
We multiply parentheses
5x-35
Back to the equation:
-(5x-35)
9x-5x+35+5=0
We add all the numbers together, and all the variables
4x+40=0
We move all terms containing x to the left, all other terms to the right
4x=-40
x=-40/4
x=-10
| -6(2x+3)(x-20)=0 | | -2+5x-7=3x-9=2x | | 7k+8=8+7k | | -4(5a+7)=7 | | x-4=2x-11+18 | | 2/6=4/x+5 | | k-1-2=-1 | | 2x+4x-3=11-1 | | (11-15)=(5x-13) | | 1x+31=20 | | 2x+9=8+4(x+2) | | 7w+9-10w=- | | -5=7-4w | | -11w=-264 | | (x^2)-121=0 | | 3(9x+5)=5(5x+9) | | (2x-7)/9=-7/10 | | 5(2t-2)=45 | | 54=24(x-10)+4(x+2) | | 2x+3(1−7x)=98 | | 9(v+2)=7v+14 | | 6j=10j−8 | | 16x-26=114+3x | | 7w-7(-19w-15)=7(18w+15) | | 5j=460 | | 17.27=3g+3.92 | | 3x+6=4(x–2)+11 | | 7p+6p+5=4p−4 | | 5x^2+15=105 | | -11h=11 | | 2(4x+5)-2x=4(x-5) | | 10/9z+1=7/8 |